Analysis of cerebrospinal fluid cells by flow cytometry: Comparison to conventional cytology - Zeman, David; Revendova, Kamila; Bunganic, Radovan; Ryzi, Marketa; Masarovicova, Petra; Kusnierova, Pavlina; Kotrlova, Vera; Hradilek, Pavel; Stejskal, David; Thon, Vojtech (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2023)
AIMS: This study compared the results obtained by basic immunophenotyping of cerebrospinal fluid (CSF) cells by flow cytometry (FC) to the results of conventional cytology and evaluated the possibility of detailed analyses of CSF B-cell subpopulations. METHODS: Samples from 42 patients were examined by conventional cytology (native and/or pre-centrifuged CSF) and FC. The results from 15 patients without evidence of organic neurological disease were used to estimate reference ranges. RESULTS: Pre-centrifugated CSF had significantly higher cell yield on the cytologic slide, but cell subpopulation percentages were altered; the percentage of lymphocytes was significantly higher and monocytes significantly lower compared to both native CSF slides and FC. The percentage of granulocytes was higher in FC compared to cytology. For leukocyte count, the following reference ranges were estimated for Fuchs-Rosenthal chamber (FR) counting and FC, respectively: leukocytes ≤4.7/μL and ≤2.5/μL, lymphocytes ≤4.1/μL and ≤1.8/μL, monocytes ≤1.2/μL and ≤0.9/μL, and granulocytes 0/μL and ≤0.2/μL. The following reference ranges were estimated for basic subpopulations: T-lymphocytes 84.1-100%, B lymphocytes 0.0-1.5%, NK cells 0.0-6.3%, NKT cells 0-9.5%, and CD3+CD4+/CD3+CD8+ 0.8-4.9. Using a volume of 1.2-2.4 mL, the number of B lymphocytes was too low (<20) in samples with ≤2.7 cells/μL in the FR. CONCLUSIONS: Even normal CSF samples are amenable to basic mononuclear cell subpopulation analysis by FC. However, analysis of the B-cell subpopulations requires either a larger sample volume or selection of samples with ≥ 3 cells/μL.
Keywords: Flow Cytometry; mozkomíšní mok; T-lymfocyty; T-Lymphocytes; B lymphocytes; Immunophenotyping; lymfocyty; průtoková cytometrie; imunofenotypizace; Humans; Leukocytes; Cerebrospinal Fluid; cerebrospinal fluid; leukocyty; cytology; Lymphocytes; lidé; flow cytometry